Rapid diagnosis of Pseudomonas aeruginosa urinary tract infections by radioimmunoassay. - Kohler, R B (1979)
A solid-phase radioimmunoassay designed to detect serotype 6 Pseudomonas aeruginosa antigens was evaluated for its ability to rapidly diagnose urinary tract infections. Twelve P. aeruginosa serotypes were easily differentiated in the assay from eight other gram-negative bacterial species. During log-phase growth, the assay detected antigens in culture when approximately 10(6) or more serotype 6 P. aeruginosa organisms were present. Both cell-associated and solubilized antigens were detected. The assay detected antigens in 13 of 17 urine specimens which grew greater than 10(5) P. aeruginosa, 3 of 38 which grew other gram-negative rods, and none of 83 with no growth. Two of the three positive specimens from the other gram-negative rod group probably also contained P. aeruginosa. No preincubation of the urine specimens was required, and results were available within 2.5 h. The assay represents an improvement over other procedures for rapidly diagnosing urinary tract infections in that it allows diagnosis by species and should be adaptable to semiautomation.